Growth estimation of the larger foraminifer Heterostegina depressa by means of population dynamics - Wolfgang Eder; Julia Woeger; Shunichi Kinoshita; Johann Hohenegger; Antonino Briguglio (PeerJ, 2019)
In Heterostegina depressa, the flagship species of laboratory investigations of larger benthic foraminifera (LBF) since the 70’s, the timing of reproduction, longevity and natural chamber building rates are still understudied. A recently developed method, the natural laboratory (sensu Hohenegger), has been applied on H. depressa populations from Sesoko Jima, NW Okinawa, Japan. An averaged chamber building rate and longevity of H. depressa were calculated based on 17 monthly samplings at fixed stations. All samples were collected at 20 and 50 m water depths using SCUBA. Live populations were dried and investigated by microCT. The monthly frequency distributions of chamber numbers and test diameters have been decomposed in normally distributed components. For each month, mean and standard deviations of the components were used to calculate the maximum chamber number and maximum test diameter. Based on these values, the natural chamber building rate (CBR) or diameter increase rate (DIR) could be estimated using the Michaelis-Menten function. CBR and DIR were inverted to estimate the ‘birthdate’ of all investigated individuals. Based on frequencies of these ‘birthdates’, main reproduction events could be detected and compared to the reproduction timing of other subtropical and tropical LBF taxa. Furthermore, peaks in reproduction could be linked to monsoon wet seasons (=“rainy seasons”) and winter rains.